Cape Verde welcomes single African market but says no to parasites - Ortet, Eva (Technical Centre for Agricultural and Rural Cooperation, 1991)
Eva Ortet is Director General of Agricultural Production in the Cape Verde Ministry of Rural Development The ACP islands states are generally in the Caribbean, the Pacific or the Indian Ocean. However there are a few islands or archipelagos off the...